An Introduction to Economics - Dobson, Stephen (New York Oxford University Press, 1998)
Introducing students to some of the key concepts used by economists, this text shows how to analyze a variety of social and economic issues. Concepts are introduced in the context of real world applications, and many macroeconomic themes are presented in
Keywords: Economics